Zero Trust Security Implementation Using DevSecOps in Cloud-Native Applications - Nadipalli, Rajesh (International Journal of Computing and Engineering, 2021)
The rapid adoption of cloud-native applications has introduced new security challenges, rendering traditional perimeter-based models inadequate. Zero Trust Security (ZTS), grounded in the principle of never trust, always verify, provides a modern framework to secure dynamic, distributed environments. This paper examines the implementation of ZTS through DevSecOps practices in cloud-native ecosystems. By embedding security into every phase of the software development lifecycle, DevSecOps enables continuous policy enforcement, automated threat detection, and rapid remediation. The study presents a reference architecture that integrates core ZTS principles such as identity verification, least privilege access, and micro-segmentation with DevSecOps tools like CI/CD pipelines, Infrastructure as Code (IaC), policy-as-code, and container orchestration platforms. A simulated case study illustrates how this integration enhances security posture, reduces attack surfaces, and improves compliance with regulatory standards. Key benefits such as improved agility and scalability, are evaluated alongside challenges like toolchain complexity and organizational alignment. The paper concludes that combining Zero Trust with DevSecOps delivers a proactive, scalable security model for modern cloud-native applications and offers a set of best practices for successful implementation.